Comparison of fluorescence biosensors and whole-cell patch clamp recording in detecting ACh, NE, and 5-HT - Zhang, Kun; Han, Yanfei; Zhang, Peng; Zheng, Yuqiong; Cheng, Aobing (Frontiers in Cellular Neuroscience, 2023)
The communication between neurons and, in some cases, between neurons and non-neuronal cells, through neurotransmission plays a crucial role in various physiological and pathological processes. Despite its importance, the neuromodulatory transmission in most tissues and organs remains poorly understood due to the limitations of current tools for direct measurement of neuromodulatory transmitters. In order to study the functional roles of neuromodulatory transmitters in animal behaviors and brain disorders, new fluorescent sensors based on bacterial periplasmic proteins(PBPs) and G-protein coupled receptors have been developed, but their results have not been compared to or multiplexed with traditional methods such as electrophysiological recordings. In this study, a multiplexed method was developed to measure acetylcholine (ACh), norepinephrine (NE) and serotonin (5-HT) in cultured rat hippocampal slices using simultaneous whole-cell patch clamp recordings and genetically encoded fluorescence sensor imaging. The strengths and weaknesses of each technique were compared, and the results showed that both techniques did not interfere with each other. In general, genetically encoded sensors GRABNE and GRAB5HT1.0 showed better sensitivity and stability compared to electrophysiological recordings in detecting NE and 5-HT, while electrophysiological recordings had faster temporal kinetics in reporting ACh. Moreover, genetically encoded sensors mainly report the presynaptic neurotransmitter release while electrophysiological recordings provide more information of the activation of downstream receptors. In sum, this study demonstrates the use of combined techniques to measure neurotransmitter dynamics and highlights the potential for future multianalyte monitoring.